Design of Load Control System using Dual Tone Multi Frequency (DTMF) with Arduino Uno - Ong Jing Kai, - (Universiti Malaysia Sarawak, 2022)
The project operates on the basis of receiving DTMF tone commands from any phone in order to remotely switch any electrical load, such as an agricultural pump, a household or industrial load, and so on. In industries, loads are dispersed across a vast region, making operation of these loads a time-consuming and challenging process. Pumps and other loads are also linked over a vast region in agricultural fields, making it difficult for the farmer to run all the loads, and similarly for household loads. Keeping these issues in mind, the suggested system utilizes DTMF technology to remotely regulate the loads. A mobile phone's audio output socket is used to interact with a DTMF decoder in the system in order to receive tone commands. The received cell phone codes are translated to digital commands using a DTMF Decoder, which determines the key's frequency and converts it to its digital counterpart, which is then sent to a microcontroller (Arduino Uno). The microcontroller will transmit signals through a buffer to activate the various loads by turning ON/OFF in response to the orders supplied from the sender's smartphone. Additionally, this idea may be upgraded by using a Wi-Fi modem, which enables load management through internet. This eliminates the stable telco network requirement for the system to function.